Un necesario marco jurídico para las actividades espaciales en Colombia. (2011)
The importance of education and dissemination of the outer space law; as a matter to be included in the programs of the law faculties or schools in Colombia; must be a present commitment. New technologies involve a parallel development of legal advances and adjustments to the relevant regulatory frameworks; including Colombia s participation to the international legal body to develop its space efficiently; which today mainly corresponds to the use of communications satellites and earth observation for the multiple benefits of citizens; regardless of the territory in which they are.